Magnetic fields in star-forming systems (I): idealized synthetic signatures of dust polarization and Zeeman splitting in filaments - Reißl, Stefan; Pellegrini, Eric William; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. We use the polaris radiative transfer code to generate predictions of the two main observables directly sensitive to the magnetic field morphology an
Gesehen am 11.12.2019